The Petition of Peter the Great for The Orthodox Christians of Venice as Part of Russia's Foreign Policy - Iastrebov Aleksei (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi, 2016)
The petition of Peter the Great for return of a taken church from the Orthodox christians of Venice is interesting in the context of the religious motives behind his domestic and foreign policy, his interaction with Catholicism, and his support of Orthodoxy in Europe and the Ottoman Empire. The charter itself is a unique document testifying to the concerns of the Russian czar for coreligionists in a Catholic country. At the same time, it is clear that in an epoch when religion was tightly intertwined with politics, such an appeal was not only part of religious but also secular politics. The goals of the Russian government in the Balkans coincide with the aspirations of the Orthodox peoples languishing under the yoke of the Turks: they had seen in Russia the liberator of the hated invaders. The natural allies of Moscow-Petersburg themselves for a long time to convince kings to stand up for the persecuted faith, and calls were heard from bishops of the Eastern Church and the authorities are dependent on the Turkish vassal principalities. Finally, the moment came. Despite the fact that Peter did not want war with the Sultan, he had to prepare for it, and for that sought to mobilize all the allies, including the Balkan Christians. The letter addressed to the Venetian Doge, actually addressed to them. Following the message the Russian government opens in Venice diplomatic agency, whose task are monitoring the political situation in Italy and the Balkans, as well as the recruitment of volunteers under the ﬂ ag of St. Andrew. Thus, the charter-petition of Peter for the Orthodox of Venice has completely fulﬁ lled its task — it has become part of a policy to win sympathy of the peoples of the Balkans, and has contributed to the understanding that the Venetian government would not object to the actions of the Russian envoys in the country.